Analysis of Local Banana Product Diversification as Market Expansion Through Digital Finance - Muhammad Rijalus Sholihin; Lia Rachmawati; Nur Andita Prasetyo (ABM: International Journal of Administration, Business and Management, 2025)
This study analyzes the diversification strategy of banana-based products in Lumajang Regency through the utilization of financial technology (fintech) and digital finance as an effort to expand markets nationally and internationally. Lumajang, as one of the largest banana producers in East Java with a production of 716,624 quintals in 2023, shows significant potential for developing value-added processed banana products. However, most small and medium enterprises (SMEs) still face challenges in product innovation, limited digital marketing, low adoption of fintech, and high logistics costs for market expansion. Using a qualitative case study approach with the CIPOO (Context-Input-Process-Output-Outcome) framework, data were collected through participant observation, in-depth interviews, and document studies. The findings reveal that although several banana-based products such as chips, banana flour, and beverages have been developed, the lack of digital literacy and financial inclusion limits their competitiveness. Digital marketing channels remain local and informal, while knowledge of export administration and packaging standards is still insufficient. The integration of fintech and digital finance is identified as a key driver to improve access to capital, enhance transaction efficiency, and expand market reach. This research concludes that intensive mentoring in product diversification, digital literacy, and export packaging is crucial to strengthening SMEs’ competitiveness and supporting sustainable development goals (SDGs) in the region.